1993
DOI: 10.1084/jem.177.4.1165
|View full text |Cite
|
Sign up to set email alerts
|

B lymphocytes may escape tolerance by revising their antigen receptors.

Abstract: SlllllmsryTo explore mechanisms that prevent autoreactivity in nonautoimmune mice, endogenous immunoglobulin (Ig) light (L) chains that associate with a transgenic anti-DNA heavy chain were analyzed. The antibodies from splenic B cell hybridomas of such mice did not bind doublestranded DNA (dsDNA) and their L chain sequences showed a biased use of V~ and J~ gene segments. The 44 L chains in this survey were coded for by just 18 germline genes. Six of the genes, each belonging to a different V~ group, were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
293
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 378 publications
(305 citation statements)
references
References 40 publications
7
293
2
Order By: Relevance
“…According to this hypothesis, recognition of foreign antigen by mature B cells induces clonal expansion and antibody secretion, and thus yields an antigen specific immune response and the induction of memory, whereas newly formed immature B cells with an auto-reactive receptor will die upon encounter with their auto-antigen. That death was inevitable for an immature B cell that had had its BCR triggered was challenged about 15 years ago by findings reported by Nemazee and colleagues [43] and Weigert and colleagues [44,45] and reviewed in [46,47]. The groups of Nemazee and Weigert independently showed that auto-reactive immature B cells upon encounter of their auto-antigen do not have to automatically die, but rather can eliminate their auto-reactive specificity and express a novel non-auto-reactive receptor by secondary V to D-J recombination events [43][44][45][46][47].…”
Section: Immature Bone Marrow B Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to this hypothesis, recognition of foreign antigen by mature B cells induces clonal expansion and antibody secretion, and thus yields an antigen specific immune response and the induction of memory, whereas newly formed immature B cells with an auto-reactive receptor will die upon encounter with their auto-antigen. That death was inevitable for an immature B cell that had had its BCR triggered was challenged about 15 years ago by findings reported by Nemazee and colleagues [43] and Weigert and colleagues [44,45] and reviewed in [46,47]. The groups of Nemazee and Weigert independently showed that auto-reactive immature B cells upon encounter of their auto-antigen do not have to automatically die, but rather can eliminate their auto-reactive specificity and express a novel non-auto-reactive receptor by secondary V to D-J recombination events [43][44][45][46][47].…”
Section: Immature Bone Marrow B Cellsmentioning
confidence: 99%
“…That death was inevitable for an immature B cell that had had its BCR triggered was challenged about 15 years ago by findings reported by Nemazee and colleagues [43] and Weigert and colleagues [44,45] and reviewed in [46,47]. The groups of Nemazee and Weigert independently showed that auto-reactive immature B cells upon encounter of their auto-antigen do not have to automatically die, but rather can eliminate their auto-reactive specificity and express a novel non-auto-reactive receptor by secondary V to D-J recombination events [43][44][45][46][47]. This process of receptor revision was then called receptor editing [43][44][45][46][47].…”
Section: Immature Bone Marrow B Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…D eveloping bone marrow (BM) 4 B cells that are strongly autoreactive may avoid elimination by changing the specificity of their Ag receptor (1)(2)(3). This process is referred to as receptor editing and usually involves secondary L chain gene rearrangement and expression of a new or additional L chain (4,5).…”
mentioning
confidence: 99%
“…This process is referred to as receptor editing and usually involves secondary L chain gene rearrangement and expression of a new or additional L chain (4,5). L chain editing was first demonstrated in mice containing Ig transgenes (tgs) that code for Abs with anti-self specificity (1)(2)(3). Subsequent studies have indicated that L chain editing may occur frequently and help shape the Ab repertoire (6,7).…”
mentioning
confidence: 99%